Osobowość katechety na podstawie wskazań ks. Mieczysława Węglewicza w świetle katechetyki współczesnej - Bąkowski, Wiesław (Collectanea Theologica, 2018)
Father Mieczysław Węglewicz was an outstanding teacher and youth minister. He is a model catechist for modern catechesis. As a teacher and a didactic, Father Węglewicz helps the students in the catechism class by finding the appropriate rules of conduct and way of life. His didactics allows the catechist to get to know the students better, thus providing a more effective catechesis.